2005
DOI: 10.1111/j.1365-2036.2005.02346.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: endoscopic variceal ligation for primary prophylaxis of oesophageal variceal bleeding

Abstract: SUMMARYBackground: The treatment effects of primary prophylactic endoscopic variceal ligation are unclear. Aim: To compare the treatment effects of endoscopic variceal ligation and b-blockers for primary prophylaxis of oesophageal variceal bleeding. In addition, a subgroup analysis was done with the purpose to delineate differences in the effects of intervention that were biologically based. Methods: We performed a literature search for randomized controlled trials, which compared the treatment effects of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(102 citation statements)
references
References 32 publications
(212 reference statements)
5
89
0
8
Order By: Relevance
“…Previous meta-analysis of trials regarding primary prophylaxis revealed that adverse events were associated with EVL in 42.7% and with beta blockers in 56.1%. 20 Moreover, serious complications were noted in 0-6.7% in patients treated with EVL and 6.7-30.3% in patients receiving beta blockers. Thus, the meta-analysis drew the conclusion that severe adverse events were significantly less in EVL compared with beta blockers.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous meta-analysis of trials regarding primary prophylaxis revealed that adverse events were associated with EVL in 42.7% and with beta blockers in 56.1%. 20 Moreover, serious complications were noted in 0-6.7% in patients treated with EVL and 6.7-30.3% in patients receiving beta blockers. Thus, the meta-analysis drew the conclusion that severe adverse events were significantly less in EVL compared with beta blockers.…”
Section: Discussionmentioning
confidence: 97%
“…Two meta-analyses of these studies have been performed and suggested that EVL is superior to beta blockers in the reduction of first bleeding episodes in cirrhosis patients with moderate to large esophageal varices, but with similar survival. 19,20 On the other hand, because EVL is potentially associated with severe complications, the superiority of EVL over beta blockers in the prophylaxis of first variceal bleeding has been questioned by hepatology experts. 21 Thus, the latest Baveno Consensus of portal hypertension suggested that EVL should be offered to patients with medium/large varices and with contraindications or intolerance to beta blockers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis suggests that VBL has greater efficacy in preventing initial bleeding with a 34% relative risk reduction than do b-blockers. However, mortality is same in both treatment groups [68]. The possible benefits of VBL in reducing initial bleeding rates need to be weighed against the low cost and ease of use of b-blockers [62].…”
Section: Recommendationsmentioning
confidence: 99%
“…The possible benefits of VBL in reducing initial bleeding rates need to be weighed against the low cost and ease of use of b-blockers [62]. Approximately 25% of patients suffer transient adverse effects following VBL such as dysphagia and chest discomfort, and there is a small risk of life-threatening bleeding from esophageal ulcerations [55,58,68].…”
Section: Recommendationsmentioning
confidence: 99%